Academic self-efficacy as a protective factor for the mental health of university students during the COVID-19 pandemic - Ampuero Tello, Nayeli Lucia (2022)
University students are vulnerable to developing mental health problems due to constant exposure to academic demands. A situation that has been exacerbated by the COVID-19 pandemic and observed in several recent studies. Therefore, current practices require further research and identification of potentially protective factors for mental health.